Effect of Boiled Cassava Leaves (Manihot esculenta Crantz) on Total Phenolic, Flavonoid and its Antioxidant Activity - Hasim Hasim; Syamsul Falah; Lia Kusuma Dewi (Current Biochemistry, 2016)
Cassava leaves (Manihot esculenta Crantz) widely used as vegetables in many regions. Cassava leaves contain many minerals such as Fe, Zn, Mn, Cu, Mg, Ca, P, K, S, contain crude protein, β-carotene and have an active compound of flavonoids, phenolic, and contain chlorophyll which is a natural antioxidant. The aims of this study were to analyze the effect of boiled cassava leaves on total phenolics, flavonoids, and its antioxidant activity. Cassava leaves extraction was done by maceration method to obtain the methanol extract and infundation method to get the water extract. Based on phytochemical test, cassava leaves contained alkaloids, flavonoids, phenolic, tannins, and saponins. The highest levels of total phenolics and flavonoids contained in the methanol extract of simplicia, 30.57 mg GAE/g and 881.33 mg RE/g, respectively. Cassava leaves extract had potential as an antioxidant with the highest inhibition of DPPH radicals produced by the methanol extract of simplicia with IC50 values of 92.10 mg/L and followed by methanol extract of boiled leaves, water extract of simplicia, and water extract of boiled leaves with IC50 144.28, 155.76 dan 170.71 mg/L , respectively. In conclusion, the process of boiling cassava leaves could reduce total phenolic, total flavonoids and antioxidant activcity.